Using a novel paradigm to examine observational fear‐learning across development. Issue 7 (23rd March 2021) - Skversky‐Blocq, Yael; Pine, Daniel S.; Shechner, Tomer
Abstract: Background: Fear‐learning through observing others begins early in life. Yet, most observational fear‐learning research has focused on adults. The current study used a novel developmentally appropriate observational fear conditioning paradigm to examine differences in observational fear‐learning among children, adolescents, and adults. Method: Thirty‐six typically developing children, 41 typically developing adolescents, and 40 adults underwent differential observational fear conditioning followed by a direct exposure test. Skin conductance response (SCR) and self‐reported fear were measured. Results: Successful differential observational fear‐learning was demonstrated in all three age groups as indexed by SCR, yet developmental differences emerged. Children showed overall higher physiological arousal during acquisition compared to adolescents and adults. Additionally, children reported less differential fear and were less successful at reporting the conditioned stimulus–unconditioned stimulus contingency compared to adolescents and adults. Finally, adolescents tended to overgeneralize their fear compared with adults. Conclusions: This is the first study to compare observational fear‐learning among children, adolescents, and adults. The novel task effectively induced observational fear‐learning, particularly among adolescents and adults. Findings revealed developmental differences that have both theoretical and clinical implications.